The significance of music in early childhood education and care of toddlers in Finland: an extensive observational study - Ruokonen Inkeri; Tervaniemi Mari; Reunamo Jyrki (Routledge, Taylor & Francis Group, 2022)
The present study investigated the role of music education in early childhood education and care (ECEC) in relation to the daily activities of children ages one to three, i.e. toddlers (N = 918) in Finnish ECEC units (N = 327). A total of 23,142 random observations were conducted. The observations focused on children’s involvement, emotional expressions, social orientations and interaction with their immediate caregiver. An independently conducted survey was used to evaluate music emphasis in groups to which the observers did not have access. The data consist of the analysis of teachers’ self-evaluations concerning the role music plays in daily activities and developmental orientations of toddlers in ECEC. The connections between the large-scale observations and independently measured music emphasis are discussed in the Results section. The results of the study highlight the importance of music in ECEC pedagogy for toddlers. The children in groups where music/singing was emphasised exhibited more sustained intense activity and less low or interrupted involvement. These groups also exhibited more positive emotions, increased social adaptation and increased social involvement with adults. Special emphasis on music enhanced the pedagogical learning environment.